Are ectotherm brains vulnerable to global warming?. (August 2021) - Beltrán, Iván; Herculano-Houzel, Suzana; Sinervo, Barry; Whiting, Martin J.
Abstract : Elevated temperatures during development affect a wide range of traits in ectotherms. Less well understood is the impact of global warming on brain development, which has only rarely been studied experimentally. Here, we evaluate current progress in the field and search for common response patterns among ectotherm groups. Evidence suggests that temperature may have a positive effect on neuronal activity and growth in developing brains, but only up to a threshold, above which temperature is detrimental to neuron development. These responses appear to be taxon dependent but this assumption may be due to a paucity of data for some taxonomic groups. We provide a framework with which to advance this highly promising field in the future. Highlights: Ectotherm brains are remarkably plastic to changes in developmental temperature; however, their physiological requirements may still make them susceptible to the higher temperatures associated with global warming. Global warming affects the development of the ectotherm brain because rising temperature stimulate neuronal activity and growth up to a certain threshold, above which it is detrimental to neuron development. Making predictions about temperature effects on neuronal development and cognition is currently hampered by what might be highly taxon-dependent effects documented in a limited number of species. We propose that studying the developmental plasticity of the ectotherm brain can help us predict how a wider range of species will respond to global warming.